Daya Saing Komoditas Unggulan Sektor Pertanian dalam Pembangunan Ekonomi Kabupaten Solok - Syahrial Syahrial; Ilham Martadona; Nurkholizah Harahap (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Agriculture is a sector that has opportunities for regional economic development. The development of a region can be done by determining superior commodities that can compete comparatively and competitively. This study aims to analyze the excellent things in the agricultural sector and the competitiveness of fantastic items in Solok Regency. The research was done in Solok Regency from May to July 2022 using Location Quotient, Dynamic Location Quotient, Shift Share Analysis, and Growth Ratio Model (MRP) analysis. The research uses secondary data, namely the production value of the food crops sub-sector, the horticulture sub-sector, and the estate sub-sector from 2016 to 2020. The analysis results show that the superior agricultural sector commodities in Solok Regency are 27 commodities, of which 14 in the future have no potential to be developed, leading things that have a competitive advantage in Solok Regency, namely as many as 16 commodities, with 12 items that are growing well. From the analysis results, the government should focus more on regional development by optimizing the progress of superior agricultural commodities that are competitive and able to improve the economy in Solok Regency.